Responsibility to Customers in the Context of Public Value Management – a German Case Study - Markus Bodemann; Marieta Olaru (Amfiteatru Economic Journal, 2014)
This paper provides results obtained within a questionnaire-based survey conducted in small to medium public administrations in Germany. The survey was carried out on the occasion of working out indicators of risks and application of risk management for public sector. The results of the questionnaire enlighten reasons for undesired deviations from plans and strategy; in addition self-estimation of internal or external factors of decisions under not-certainty and their ramifications to the sustainable execution of obligatory and voluntary tasks. Hence the results are helpful to enlighten customer responsibility.
Keywords: H41; 330; Responsibility to customers; public administration; public value management; sustainable customer satisfaction; Germany